Analysis of Microporosity in Ordered Mesoporous Hierarchically Structured Silica by Combining Physisorption With in Situ Small-Angle Scattering (SAXS and SANS). - Mascotto, Simone; Wallacher, Dirk; Brandt, Astrid; Hauss, Thomas; Thommes, Matthias; Zickler, Gerald A.; Funari, Sergio S.; Timmann, Andreas; Smarsly, Bernd M. (Langmuir, 2009)
The combination of physisorption expts. with simultaneous in situ small-angle x-ray and neutron scattering (SAXS/SANS) was used to elucidate the porosity in mesoporous silica with a trimodal pore structure. The material (KLE-IL) contains spherical mesopores of 14 nm in diam., worm-like mesopores (2-3 nm), and micropores, templated by a block copolymer and an ionic liq. surfactant, while the micropores originate from the hydrophilic block of the block copolymer. The main objective of the study was the quantification of the microporosity and the small mesopores and to find out if they are indeed located between the larger, spherical mesopores. The in situ SAXS/SANS expts. took advantage of contrast matching of nitrogen (SANS, T = 77 K) and dibromomethane (SAXS, T = 290 K). By using the latter gas with a slightly larger kinetic diam., it was possible to judge the accessibility of the pores under ambient conditions. The in situ expts. were supported by high-precision ex situ physisorption. Using suitable approaches for the SAXS/SANS anal., it was possible to sep. the content of the micropores and small mesopores. [on SciFinder(R)]
Keywords: silica porosity physisorption